Working towards least restrictive environments in acute mental health wards in the context of locked door policy and practice. (5th December 2018) - Fletcher, Justine; Hamilton, Bridget; Kinner, Stuart; Sutherland, Georgina; King, Kylie; Tellez, Juan Jose; Harvey, Carol; Brophy, Lisa
Abstract: There has been a shift towards provision of mental health care in community‐based settings in Australia. However, hospitals continue to care for people in acute mental health wards. An increasing proportion of the people in wards are admitted involuntarily, subject to restrictions of movement to minimize risk of harm to self and others. In response to concerns about the safety of people absconding from care, Queensland Health introduced a policy requiring all acute mental health wards in the State to be locked. In response, the Queensland Mental Health Commission funded a project to understand the impact of this policy and develop evidence‐based recommendations regarding provision of least restrictive, recovery‐oriented practices in acute wards. Facilitated forums were conducted with 35 purposively selected participants who identified as consumers, carers, or staff of acute mental health hospital wards, to test the acceptability, feasibility, and face validity of a set of evidence‐informed recommendations for providing least restrictive, recovery‐oriented practices. Participant responses were recorded, and data were analysed through an inductive, thematic approach. A recovery‐oriented approach was supported by all stakeholders. Reducing boredom and increasing availability of peer support workers were considered key to achieving this. Focusing less on risk aversion was reported as central to enabling true Recovery Orientation. This project enabled recognition of the perspectives of consumers, carers, and staff in the consideration of evidence‐informed recommendations that could be implemented to provide least restrictive care in the context of locked doors.